Managing cyber resilience literacy for consumers - Antipova, Tatiana; Riurean, Simona (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
It seems inevitable that digitalization will have a profound and irreversible impact on our lives, and it seems reasonable to suppose that our world will never be the same again. Objectives of this study is to gain insight into consumers’ understanding of cyber security threats and their willingness to enhance their cyber resilience. To achieve this, a survey was conducted using AI tools such as Open ChatGPT, Copilot and PI. The survey was distributed selectively among consumers via Google Form. The results of the survey conducted during the study indicated that the majority of respondents (72%) expressed interest in attending online interactive seminars to gain more knowledge about managing cybersecurity threats. However, respondents with the lowest cyber resilience knowledge did not express the same level of interest. With technology becoming an increasingly important aspect in our everyday lives, it is becoming ever clearer that cybersecurity posture relies on the behavior consumers and organizations. Based on the rule that ‘never trust, always verify’ we designed ‘cybersecurity zero-trust framework model’ for consumers that allows them to protect themselves against cybersecurity threats. In an ever-shifting landscape of cybersecurity, it is important to recognize the value of continuous education as a necessity, not just an option.